Strategi Iklan Online (Studi Iklan Shopee di Media Sosial) - Desita Catur Setyo Pramesti; Nur Siyami; Anes Arini (STIE Rajawali Purworejo, 2024)
The business world in 2020 is said to be a golden year. There is no end to discussing business developments in the country. This is because Indonesia itself is a country that has extraordinary business development potential. Many analysts and observers say that Indonesia is a very large market to be a good habitat for business development followed by the development of the existing internet. Shopee is a buying and selling site or online market place that specifically provides buying and selling transactions. These advertisements often appear on internet or online social media. Likewise with the public, when they see Shoope advertisements in online media, many consumers are interested and carry out buying and selling transactions. They often buy products such as clothes, beauty equipment and other accessory products. Shopee advertisements appear almost all the time on Social Media, Shopee advertisements also offer discounts, free shipping and quality goods.